PERANCANGAN STASIUN KERJA ERGONOMI UKM SINAR MUTIARA DESA KARANG SERANG KABUPATEN TANGERANG - Sartono Sartono; Yogi Priyo Istiyono; Siti Fatimatul Zuhro; Raden Hernadi; Nirfison Nirfison; Kartika Sari Dewi; Nudrotul Kamilah (Jurnal Abdimas Bina Bangsa, 2023)
Ergonomic workstation design is important to increase efficiency and productivity at UKM Sinar Mutiara. This study aims to identify ergonomic problems faced by workers at current workstations and design appropriate ergonomic solutions. Methods of observation, interviews, and data analysis were used to understand the needs and challenges faced. The results of the study show that workers experience discomfort and fatigue due to less-than-optimal workstation design. Ergonomic workstation design will involve the use of height-adjustable desks, chairs with back support, and monitors that can be adjusted to their position. In addition, workstation layouts will be improved to minimize repetitive motions that can potentially cause injury. The implementation of this design is expected to improve the comfort and health of employees, as well as improve productivity and quality of work at Sinar Mutiara UKM Keywords: ergonomic workstation, Sinar Mutiara UKM, efficiency, employee health, productivity